Eukaryotic ribosome assembly, transport and quality control - Peña, Cohue; Hurt, Ed; Panse, Vikram (Nature structural & molecular biology, 2017)
Eukaryotic ribosome synthesis is a complex, energy-consuming process that takes place across the nucleolus, nucleoplasm and cytoplasm and requires more than 200 conserved assembly factors. Here, we discuss mechanisms by which the ribosome assembly and nucleocytoplasmic transport machineries collaborate to produce functional ribosomes. We also highlight recent cryo-EM studies that provided unprecedented snapshots of ribosomes during assembly and quality control.
Gesehen am 11.07.2018